Sensory analysis and physicochemical characterization of Boursin cheese from milk of goats fed increasing levels of cassava chips - Marques, Raquel Ornelas [UNESP]; Gomes, Helen Fernanda Barros; Brito, Evelyn Prestes [UNESP]; Cañizares, Gil Ignacio Lara; de Lima Meirelles, Paulo Roberto [UNESP]; Rodrigues, Luciana [UNESP]; Betelli, Rafael Gaya Latorre [UNESP]; Gonçalves, Heraldo Cesar [UNESP] (Revista Brasileira de Zootecnia, 2024)
The objective of this study was to examine the physicochemical composition and sensory properties of Boursin cheese made from the milk of goats fed diets with increasing levels of cassava chips replacing corn. Eight lactating Alpine goats were distributed into two 4 × 4 Latin squares, where they were subjected to diets in which 0, 33, 66, and 100% of corn was replaced with cassava chips. The cheeses were prepared with individual milk of each goat for physicochemical, yield, and texture analyses. Sensory analysis consisted of flavor and texture appraisal by 50 untrained tasters, using the difference-from-control test and the acceptance test. The cheeses from the four treatments did not differ in their fat, protein, and total solid contents; acidity; moisture; ash; pH; yield; or the texture parameters of gumminess, cohesiveness, hardness, and chewiness. They also showed no difference in the sensory acceptance of flavor and texture, indicating that the panelists did not perceive the replacement of corn with cassava chips.
Keywords: acceptability; alternative food; cost; proximate composition; texture; yield